Translating Foreign Languages and Non-Native Varieties of English in Animated Films: Dubbing Strategies in Italy and the Case of Despicable Me 2 - Minutella, Vincenza (Journal of Audiovisual Translation, 2020)
The aim of this paper is to explore how foreign languages (i.e., languages other than English) and non-native varieties of English are used in Anglo-American animated films and to investigate the strategies adopted in Italian dubbing to deal with such multilingual features. The paper combines insights into professional practice with a close examination of a specific case study. The film Despicable Me 2 (dir. Pierre Coffin, Chris Renaud, Illumination Entertainment, 2013) has been chosen for analysis since it displays more than one language and several language varieties (British English, American English and foreign-accented English). The film also exploits visual and verbal stereotypes which enhance the comedic elements of the film. This multiplicity of voices and identities through language variety represents a challenge for audiovisual translators. By analysing the representation of characters and drawing on personal communication with Italian dubbing practitioners, the article aims to unveil how linguistic variation, multilingualism and diversity are dealt with in dubbing. The article will show that, although general trends may be identified as far as foreign languages and non-native varieties are concerned, the solutions offered by dubbing professionals often depend on a variety of factors and agents.